2020
DOI: 10.18844/cjes.v15i5.5193
|View full text |Cite
|
Sign up to set email alerts
|

Should I ask for help? The role of motivation and help-seeking in students’ academic achievement: A path analysis model

Abstract: Abstract Academic achievement is considered as one of the major factors in the learning process, as it is one of the complex variables that have an important influence on learning. The purpose of the current study was to investigate the relationship between academic motivation, academic help-seeking and academic achievement. A total of 437 university students were selected randomly (simple random–online questionnaires) from many Arab countries (Jordan, Kingdom of Saudi Arabia, United Arab Emirates and Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Academic motivation is one of the internal processes that include: a person's desire to optimize his efforts and his preferences in studying and his tasks. Motivation is also divided into 2, the first is intrinsic motivation, namely the need for achievement and the second is extrinsic motivation, which includes fear of failure, socialization between friends, and expectations of others [9]. in the research of [10], they also used the path analysis method to develop the concept of oral healthrelated quality of life (OHRQoL) which has 4 dependent and 4 independent variables.…”
Section: Regression Modelmentioning
confidence: 99%
“…Academic motivation is one of the internal processes that include: a person's desire to optimize his efforts and his preferences in studying and his tasks. Motivation is also divided into 2, the first is intrinsic motivation, namely the need for achievement and the second is extrinsic motivation, which includes fear of failure, socialization between friends, and expectations of others [9]. in the research of [10], they also used the path analysis method to develop the concept of oral healthrelated quality of life (OHRQoL) which has 4 dependent and 4 independent variables.…”
Section: Regression Modelmentioning
confidence: 99%
“…In other words, distance learning provides the opportunity to learn at the desired age, place and time, at the desired speed, using the desired environment. Features such as distance, time, place, age, socio-economic status, physical disability keep distance education and lifelong learning are always on the agenda (Algharaibeh, 2020;Riga et al, 2020).…”
Section: Distance Learningmentioning
confidence: 99%
“…According to Self Determination Theory (SDT), people are born with an innate instinct to act (Ryan & Deci, 2000a). However, it is not always possible for people to act with intrinsic motivation (Algharaibeh, 2020). Therefore, the motivation that drives a person can arise not only from one's internal resources but also from external sources (Manchanda, 2017).…”
Section: Motivationmentioning
confidence: 99%
“…e results confirmed the validity of the AMS as a measure of motivation. Algharaibeh [49] investigated the psychometric properties of the AMS in the Jordanian environment, and the results showed that the AMS has an acceptable validity and reliability.…”
Section: Academic Motivation Scale (Ams)mentioning
confidence: 99%